Control of surface potential and hydroxyapatite formation on TiO2 scales containing nitrogen-related defects. (15th August 2018) - Hashimoto, Masami; Ogawa, Takafumi; Kitaoka, Satoshi; Muto, Shunsuke; Furuya, Maiko; Kanetaka, Hiroyasu; Abe, Masayuki; Yamashita, Hayato
Abstract: The hydroxyapatite (HAp) formation ability and related surface potentials of rutile-type TiO2 scales formed on Ti are controlled by varying the Ti heat treatment conditions in a N2 atmosphere containing a trace amount of O2 . The zeta potentials of the samples heated at 873 and 973 K for 1 h are large negative and positive values, respectively, where HAp formation on the surface is enhanced in both cases. Upon longer heat treatment at those temperatures, the HAp forming ability diminishes and the zeta potential becomes more neutral. Kelvin probe force microscopy indicates that, under dry conditions, the surface charges on the TiO2 scales formed at 873 and 973 K in 1 h are positive and negative, respectively, opposite to the signs of the zeta potentials measured under wet conditions. Scanning transmission electron microscopy, electron energy loss spectroscopy, and calculations of defect formation energies reveal that nitrogen atoms incorporated into TiO2 during scale formation produce the charged defects ( N O ) O − 1 and ( N 2 ) O + 2 for the scales formed in 1 h at 873 and 973 K, respectively. In the case of longer treatments, nitrogen-related defects presumably transform into more stable states, such as N2 gas, in voids, resulting in a neutral surface. The present findings lead to physical models of surface charge distributions that elucidate the relationship between nitrogen-related defects, charged surfaces, and HAp formation mechanisms. Graphical abstract: Image 1